Updated Database and Trends of Declared Low- and No-Calorie Sweeteners From Foods and Beverages Marketed in Spain - Samaniego-Vaesken, Mª de Lourdes; González-Fernández, Beatriz; Partearroyo, Teresa; Urrialde, Rafael; Varela-Moreiras, Gregorio (Frontiers in Nutrition, 2021)
Background: The past few years have witnessed an increase in the availability of food products containing one or more low- and no-calorie sweeteners (LNCS) in the Spanish market, mostly due to the new massive reformulation plan. However, these are not included in food composition tables or databases, and therefore assessment of their intake amongst the population is complex. Our aim was therefore to update a database including commercialized foods and beverages. Method: A systematic search of ingredient information from the different food and beverage categories was undertaken during 2019 by recording the availability and type of LNCS declared in product’s information from labels and retailer’s on-line shopping platforms from Spain to update a previous food composition database compiled in 2017. Results: A total of 1,238 products were identified. Major groups were sugar and sweets (24%), non-alcoholic beverages (21%), cereals and grains (19%) and milk and dairy products (14%) accounting for >70% of total products. Mainly declared LNCS were sorbitol (19.5%), sucralose (19.5%) and acesulfame K (19.2%). Conclusion: There is a widespread variety of products that include LNCS as an ingredient and a higher availability than when compared to 2017, consequently it might be expected that LNCS are commonly consumed at present in the Spanish diet.